MANAJEMEN SARANA DAN PRASARANA DI SEKOLAH MENENGAH ATAS (SMA) NEGERI TITIAN TERAS MUARO JAMBI - Sri Marmoah (Universitas Batanghari Jambi, 2014)
The research was conducted at SMAN N Titian Teras Muaro Jambi, observe the implementation of facilities and infrastructure in the school environment as a whole. The principal issue in this study is: why management infrastructure in SMAN N Titian Teras Muaro Jambi not meet the regulations of the Minister of National Education No. 24 of 2007 on the Standard Means Infrastructure School. To answer the research problem, this study uses descriptive qualitative research methods. Data collection efforts by using the method are observation, interview, and documentation. Furthermore, the data collected and analyzed data through the steps of data reduction, data display, and conclusion.From the results of this research found that first, the facilities and infrastructure management in SMAN N Titian Teras Muaro Jambi is optimal, where the principal do the planning, implementation, and evaluation of educational facilities properly. Second, the factors inhibiting the implementation of the infrastructure consist of internal factors, namely low resource principal. While external factors, namely the lack of supports of the Department of Education, limited funding and lack of cooperation with the school committee. Third, the principal effort was made to improve the educational facilities in SMAN N Titian Teras Muaro Jambi is improving educational facilities, in coordination with the Department of Education and the school committee The results of this research was recommended to the parties as follows: first, directed the District Education Office Muaro Jambi as the high school coaches in the district Muaro Jambi, is expected to provide optimal support and attention to facilities and infrastructure at SMAN N Titian Teras Muaro Jambi. Second, the principal must implement management infrastructure that is open to improve infrastructure performance management to become the international standard schools. Third, the public is expected to play an active role in providing input and support both morally and sprituil to improve facilities and infrastructure.Keyword : management, facilities and infrastructure